Impact of lifting school mask mandates on community SARS-CoV-2 cases, hospitalizations, and deaths: a retrospective observational study - Zeynep Ertem; Anseh Danesharasteh; Sonia T. Anand; Nicholas J. Jackson; Richard E. Nelson; Richard E. Nelson; Elissa M. Schechter-Perkins; Lloyd Fisher; Lloyd Fisher; Shira Doron; Westyn Branch-Elliman; Westyn Branch-Elliman; et al. (Frontiers in Public Health)
BackgroundSchool masking mandates were widely adopted as a pandemic control measure, however, limited data are available regarding their effectiveness as a strategy for reducing burden of disease in the surrounding community.ObjectiveTo evaluate the impact of school masking policy de-adoption (mask-lifting) on SARS-CoV-2 incidence rates, hospitalizations, and deaths in the surrounding community.MethodsDesign: Retrospective observational study with an event study design, a difference-in-difference method; a target trial emulation (TTE) framework was applied as a secondary analysis. Cohort creation: Data collected from 9/2021 to 6/2022 on SARS-CoV-2 cases, hospitalizations, deaths and vaccination rates were combined with district-level masking policy data. Analysis: In the event study, the impact of masking policy de-adoption on SARS-CoV-2 cases per 100,000 county residents stratified by age during the 8-week period following the policy change was estimated. Effects on hospitalization and deaths per 1,000,000 residents were secondarily estimated. In a secondary analysis, a target trial emulation framework was applied to estimate average treatment effects.ResultsN = 3,970 districts composed of 53,453 schools were included in the cohort. In the event study, no consistent trends for COVID-19 case rates were identified for the whole cohort or for any age group. For the whole cohort, there was a statistically significant increase found 6–8 weeks following the policy change (maximum increase, 1.91 hospitalizations per 1,000,000 county residents); increases in hospitalizations were also found in the stratified analysis for all age groups, although absolute impacts were small. An increase in deaths was found during the period from 4 to 7 weeks following the policy change (maximum increase 0.62 deaths per 1,000,000 residents). In the stratified analysis, small increases in death rates were seen in 50–69 year olds (range, 0.088–1.49) and >70 year olds (range, 0.23–2.58) but not in younger groups. In the TTE framework, cases, hospitalizations, and deaths were similar in control and intervention counties.ConclusionThis study evaluating the impact of lifting of mask mandates in schools, analyzed in two ways, was consistent results ranging from no impact to a small but statistically significant impact of the policy change on SARS-CoV-2 case and severe outcomes rates in the surrounding community. Findings can be used to inform future pandemic policy responses for elementary and secondary schools.